Analisys of Sabar And Syukur Material In Al-Qur’an Hadith Learning At Islamic Junior High School - Suhefri, Suhefri; Adona, Putri (International Journal of Research, 2024)
Patience and gratitude are the responses of believers to the destiny that Allah SWT has determined. Where as proof of faith in the decrees of Allah SWT, when disaster strikes they are patient, and if they get pleasure they are grateful. Based on this, in this research the author wants to describe the material of patience and gratitude in Al-Qur'an Hadith learning. The method used in this research is a qualitative method with a content analysis approach where the main source is the Al-Qur'an Hadith Textbook for Islamic Junior High School published by the Indonesian Ministry of Religion. After conducting in-depth research, the author found that the material on Patience and Gratitude is divided into three sub-themes, namely: i) the meaning of patience and gratitude, ii) the virtues of patience and gratitude, iii) the basic concepts of patience and gratitude. Through this article, the author hopes that from this research the latest research ideas will emerge for the development of science, especially the Qur’an Hadith learning.